2017
DOI: 10.1007/s00223-017-0318-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone Health is Maintained, While Fat Mass is Reduced in Pre-pubertal Children with Obesity Participating in a 1-Year Family-Centered Lifestyle Intervention

Abstract: Diet and physical activity (PA) influence bone health in children. This study tested whether increasing milk and milk products and weight-bearing types of PA favorably changed bone outcomes assessed by dual-energy X-ray absorptiometry (DXA) and bone biomarkers in children with obesity participating in a 1-year family-centered lifestyle intervention. Children were randomized to one of three groups: Control (Ctrl; no intervention), Standard treatment (StnTx: two servings milk and milk products/day; meet PA guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The full-text review excluded 17 publications for various reasons ( Supplemental Appendix ). Finally, 21 [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ] publications were included in the present meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The full-text review excluded 17 publications for various reasons ( Supplemental Appendix ). Finally, 21 [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ] publications were included in the present meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included RCTs are reported in Supplemental Table 1 . BMC and aBMD were measured by Lunar [ 8 , 10 , 12 , 15 ], Hologic [ 9 , 14 , 23 , 25 ], or Norland [ 13 , 18 , 27 ] DXA. Nine [ [8] , [9] , [10] , 13 , 15 , 17 , 18 , 24 , 25 ] RCTs enrolled only girls, 1 [ 12 ] enrolled only boys, and 11 [ 7 , 11 , 14 , 16 , [19] , [20] , [21] , [22] , [23] , 26 , 27 ] enrolled boys and girls (but sex-specific analysis was not performed).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies investigating the association between milk and milk-product consumption and body growth, such as height, weight, and body composition, during childhood and puberty have reported inconsistent results (7)(8)(9)(10)(11). Evidence from a 1-y family-centered lifestyle intervention study investigating the impact of milk and milk-product consumption on prepubertal children with obesity reported that fat mass percentage was significantly decreased among children who consumed 4 servings milk and milk products/d compared with a control group (10). However, a longitudinal cohort study in children from ages 10 to 13 y reported lessfavorable changes in body weight and body fat for normal or overweight children consuming flavored milk compared with nonconsumers over a 2-y period (11).…”
Section: Introductionmentioning
confidence: 99%